"Because Hongkongers Should Support Hong Kong": Entanglement of National Identity, Political Ideology, and Football Fandom in Hong Kong. (June 2023) - Chung, Sanho
In this article, I argue that there can be an intersection between the rise and development of sports fandom, national identity, as well as political ideology. I contend that the rise of nationalist sports fandom can be driven by the emergence of the nationalist democratic movement. With an ongoing nationalist democratic movement against a cultural dominant "other" as the context, sports fandom becomes a container for nationalism and a reactive form of resistance against the dominant "other" who endangers them. Fans who have a stronger sense of "self" national identity and more political experience in the movement would see sports fandom as a subtle means of catharsis to counter the threat. I showcase the idea using the rise of collective fandom in the Hong Kong men's national football team in recent years as an example. I will trace how the development of the democratic movement and nationalism in Hong Kong paralleled the blossoms of the Hong Kong (men's) national football team (HKNFT) fandom over the last few years, and how the HKNFT fandom was transformed gradually into a reactive form of resistance against threats to political autonomy of Hong Kong and attempts of cultural assimilation from China. Multiple sources of data, including an onsite survey, focus group interviews, individual interviews, and secondary historical works will be utilized to support my arguments.